DIFFERENCES BETWEEN THE MOTOR STATUS OF YOUNG PREPUBESCENT BOYS AND GIRLS - Sasa Markovic; Kristina Markovic; Kramskoj Sergej (Kharkov National Pedagogical University, 2011)
A battery of tests was used on a sample of 78 preschool boys and 81 girls to evaluate the motor status. The aim of the study was to determine the differences in motor status in relation to gender. The results of the multivariate analysis of variance have indicated that significant differences exist in the entire system of variables. At the univariate level, differences were found in 5 of the 7 variables, where the boys scored higher values for the standing depth jump variable (MSDM), the 20 m run (TR20m), the polygon backwards (MPOL), while the girls showed higher values for the tests of hyper extensions (MDPK) and torso lifts for 60 sec (MPOD). The obtained results come as a consequence of biological factors on the one hand and sociological factors on the other.